Social media use and mental health in deaf or hard-of-hearing adults—Results of an online survey - Schäfer, Karolin; Miles, Felix (Frontiers in Communication, 2023)
This paper presents the results of an online survey on digital participation through the use of social media of n=38 German deaf or hard-of-hearing (DHH) adults. In addition, information about the respondents' mental health is collected with four different scales: the Rosenberg Self-Esteem Scale (RSES), the Fear of Missing Out Scale (FoMoS), the Patient-Reported Outcomes Measurement Information System Social Isolation Scale (PRO-MIS SI-S) and the Social Media Disorder Scale (SMDS). Correlation analyses using Pearson correlation and Spearman rank correlation tests were conducted to identify relationships between mental health and use of social media. The results indicate that the DHH adults have 4.13 social media accounts on average and use social media 3.78 hours per day. This is consistent with other research findings, so that the DHH individuals in this study do not differ from other DHH adults or hearing adults in the number of their social media accounts and in their media usage time. However, there are differences in usage of social media that concern, for example, the social media platforms that are used and time of usage due to communication modality (spoken language, sign language, bimodal bilingualism and mixed forms). DHH individuals who use sign language use social media less overall compared to DHH people who use spoken language. In terms of mental health, it was found that, as expected, addictive social media behavior and high usage time are interrelated. Addictive behavior, in turn, is often associated with low self-esteem, a sense of social isolation, and a fear of missing out. In general, many participants in the study score high in scales for self-perception of social isolation and loneliness. Nevertheless, there are also positive effects and opportunities of using social media, especially in terms of digital participation, for DHH people, which are also discussed in the article.